DUALISME KEPEMIMPINAN KEPALA SKPD KABUPATEN SARMI TAHUN 2015/2016 - Lazarus Yogi, Reinhard; Bandiyah, Bandiyah; Jayanthi Mertha, Anak Agung Sagung Mirah Mahaswari (Jurnal Nawala Politika, 2020)
ABSTRACT This research was conducted in Sarmi Regency with the probem of the head SKPD dualism in 2015/2016.The purpose of this research describe in detail the dualism leadership of the head SKPD Sarmi in 2015/2016. This research use d contingency theory and qualitative methods, data collection done through observation and interviews. Based results analysis, find the process of implementing the appointment or dismissal structure in the bureaucracy in Sarmi Regency is unconstutional and indicated political dynasties. The style of leadership in Sarmi is autocratic with the powerful political influence make bureaucracy is directive.The consequence is there is an illegal policy issued of the regeneration with the unilateral SKPD head being stated overlapping the SKPD head resulting from the appointment of the acting regent who is based on the minister of home affairs decree and the result of the appointment of the regenthead based on the strength of his position.   Keywords : dualism , leadership , bureaucracy , political power .